River pollution : Case study in Sungai Perai / Nor Hidayah Ismail - Ismail, Nor Hidayah (2006)
The crucial environmental issue that needs to be overcome is river pollution. River pollution is one of a major problem that had been carried out in this case study. One river catchments in Pulau Pinang that is Sungai Perai have been chosen to show the pollution information on how rivers are badly polluted. The objective of this research is to produce the Water Quality Index for this river. The index value will then identify the status of the water quality of the river. A laboratory work has to be done to determine the water parameters based on biochemical oxygen demand, chemical oxygen demand, dissolved oxygen, ammonia nitrogen, suspended solids and pH. From the analysis, the water quality of Sungai Perai is categorized as Class III. This research reviews the water quality of Sungai Perai resulting from land uses activities needs concern for the more sustainable management of river water quality and protecting valuable water resources.